Employing the Block Fourier algorithm for solving the LMMSE receiver equation under variable channel conditions - Silva, J. C. (2015)
The LMMSE (Linear Minimum Mean Square Error) algorithm are one of the best linear receivers for DS-CDMA (Direct Sequence-Code Division Multiple Access). However, for the case of MIMO/BLAST (Multiple Input, Multiple Output / Bell Laboratories Layered Space Time) with high loading, the perceived complexity of the LMMSE receiver is taken as too big, and thus other types of receivers are employed, yielding worse results. In this paper, we investigate the complexity of the solution to the MIMO LMMSE receiver's equations using Block-Fourier algorithms, for both steady and unsteady channel situations.